Variations in incubation temperature on the physicochemical characteristics of Greek yogurt with the addition of aloe vera extract (Aloe barbadensis Miller) - Irwanti, Lula Kamalia; Prastujati, Anis Usfah; Khirzin, Muhammad Habbib; Prayitno, Salvian Setyo; Amaniyah, Maghfirotul (Jurnal Agrotek Ummat, 2025)
Aloe vera ekstract is an ingredient that has many benefits, but currently there is no specific research on the use of aloe vera juice in making Greek yogurt. This study aims to determine the effect of variations in incubation temperature on the physicochemical properties of Greek yogurt with the addition of aloe vera ektract. The design used in this study is a non-factorial completely randomized design with 3 treatments and 5 replications. The treatment consists of P1 = incubation temperature 43°C, P2 = incubation temperature 46°C, and P3 = incubation temperature 49°C. The parameters observed include viscosity, yield, pH, water content, protein content, and fat content. The results showed that differences in incubation temperature had a significant effect (P < 0.01) on the value of viscosity, yield, pH, water content, and fat content but did not significantly affect the protein content of Greek yogurt with aloe vera extract, which was 8.85% - 8.95%. The best treatment was found in P3, namely an incubation temperature of 49°C.